The Effect of Number of Poles on the Output Power of Perpetual Power Generator - Chaniago, Fasha Islamay; Indra Kurniawan, Bakti; Hadi Susilo, Sugeng; Arif Nur Huda, Muhammad; Rohman, Fatkhur; Islamay Chaniago, Fasha (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
This study aims to analyze the effect of the number of poles on the output power of the Permanent Power Generator (PPG). PPG is an innovative renewable energy system that utilizes permanent magnets to generate continuous electrical power without relying on external fuel sources. This study uses an experimental approach using 1 mm diameter wire and three pole configurations (3, 6, and 9 poles) to determine the optimal configuration to maximize power output. Voltage and current measurements were taken using a digital multimeter, and the power output was calculated using the formula P=V×I. The results showed that an increase in the number of poles significantly increased the generator's power output. The highest performance was achieved with a 9-pole configuration and a 1 mm wire diameter. These findings support the basic principles of electromagnetism, where a decrease in coil resistance and an increase in magnetic field frequency contribute to higher energy conversion efficiency. This study is expected to contribute to the development of environmentally friendly power generation systems and serve as a valuable reference in the design of high-power, high-efficiency generators for future renewable energy technologies.